Leachate of landfill Smiljevići (Sarajevo, BiH) and their environmental status - Mahmutović, Omer; Prazina, Nedzad (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2023)
Leachates are produced as a filtrate from waste landfills as a result of highly polluted waters. Organic substances that are mostly present are: phenolic compounds, halogen organic substances, oils and fats. The presence of nitrogen substances is significant, followed by phosphoric substances, sulfates, chlorides, and heavy metals. Sanitary landfill "Smiljevići", created 60 years ago, is placed on the hill area of Novi Grad municipality, Sarajevo. In that time area around landfill was very sparsely populated. Following the legislative, the leachate from the Smiljevići landfill does not have a good environmental status. On the other hand, according to global - typical values, contaminant concentrations are much closer to low than average values. The content of contaminants with long retention in nature and tendency to bioaccumulation is within legal limits. Most parameters that exceed the permitted values include usually biodegradable compounds that the stream of the river Bosnia can absorb better than the small ecosystem of the Lepenički creek. The problem is further aggravated bz the fact that the area surrounding the creek is now relatively densely populated, the stream has a small water capacity, especially in the summer, and the contaminants are mostly volatile. Finally, this problem also can be attributed to irresponsible activity of urban planning.